2023
DOI: 10.1002/jcp.31021
|View full text |Cite
|
Sign up to set email alerts
|

Vascular calcification in CKD: New insights into its mechanisms

Abstract: Vascular calcification (VC) is a common complication of chronic kidney disease (CKD) and contributes to an increased risk of cardiovascular morbidity and mortality.However, effective therapies are still unavailable at present. It has been well established that VC associated with CKD is not a passive process of calcium phosphate deposition, but an actively regulated and cell-mediated process that shares many similarities with bone formation. Additionally, numerous studies have suggested that CKD patients hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 185 publications
0
6
0
Order By: Relevance
“…For example, the abnormal calciumphosphate homeostasis, inflammation, oxidative stress, and dysregulation of FGF23-Klotho axis is shown to involved in pathogenesis of vascular calcification. 22 Previous studies have shown that both high phosphate and oxidative stress have impacts on HDAC2 expression at transcriptional or posttranscriptional level. 23,24 Therefore, we speculated that increased phosphate in CKD might be a major cause of the reduction of HDAC2 in VSMCs of the artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the abnormal calciumphosphate homeostasis, inflammation, oxidative stress, and dysregulation of FGF23-Klotho axis is shown to involved in pathogenesis of vascular calcification. 22 Previous studies have shown that both high phosphate and oxidative stress have impacts on HDAC2 expression at transcriptional or posttranscriptional level. 23,24 Therefore, we speculated that increased phosphate in CKD might be a major cause of the reduction of HDAC2 in VSMCs of the artery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the vascular calcification in CKD is a consequence of multiple risk factors. For example, the abnormal calcium‐phosphate homeostasis, inflammation, oxidative stress, and dysregulation of FGF23‐Klotho axis is shown to involved in pathogenesis of vascular calcification 22 . Previous studies have shown that both high phosphate and oxidative stress have impacts on HDAC2 expression at transcriptional or posttranscriptional level 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements highlight abnormalities in epigenetic modifications (such as DNA methylation, histone modifications, and noncoding RNAs), ferroptosis of VSMCs, autophagy dysfunction, and senescence as active participants in the cellular processes leading to VC ( 12 , 20 , 21 ). Extensive studies have delved into the involvement of senescent vascular cells, including VECs, VSMCs, and macrophages, in propagating senescence through paracrine mechanisms (e.g., SASP and MV) ( 22 24 ).…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Vascular calcification (VC) is a pathological process characterised by the deposition of hydroxyapatite crystals in the layer of the arterial wall that increases the risk of cardiovascular (CV) events [1]. VC is a hallmark of vascular remodelling induced by physiological ageing, diabetes, atherosclerosis, and chronic kidney disease (CKD) [1][2][3]. Anatomically, there are two types of VC.…”
Section: Introductionmentioning
confidence: 99%